(untitled) (Ameghiniana, 2013)
A comparative analysis of the skeIeton of the genera Herrerasaurus and Siaurikosaurus is made. The result suggests that its was closely related and shows many differences with other triassic saurischians, principally in the pelvic girdle and hinds limbs. The genera Herrerasaurus and Staurikosaurus are placed in a new family, Herrerasauridae. A definition of this new family is given. Its placement in the major taxa of the Order Saurischia is briefly discussed.